Critical incidents, nocturnal supervision, and caregiver knowledge on SUDEP in patients with Dravet syndrome: A prospective multicenter study in Germany - Maltseva, Margarita; Rosenow, Felix; Schubert-Bast, Susanne; Flege, Silke; Wolff, Markus; von Spiczak, Sarah; Trollmann, Regina; Syrbe, Steffen; Ruf, Susanne; Polster, Tilman; Neubauer, Bernd A.; Mayer, Thomas; et al. (Epilepsia, 2023)
Objective: The aim was to investigate the monitoring, interventions, and occurrence of critical, potentially life-threatening incidents in patients with Dravet syndrome (DS) and caregivers’ knowledge about sudden unexpected death in epilepsy (SUDEP). Methods: This multicenter, cross-sectional study of patients with DS and their caregivers in Germany consisted of a questionnaire and prospective diary querying the disease characteristics and demographic data of patients and caregivers. Results: Our analysis included 108 questionnaires and 82 diaries. Patients with DS were 49.1% male (n = 53), with a mean age of 13.5 (SD ± 10.0 years) and primary caregivers were 92.6% (n = 100) female, with a mean age of 44.7 (SD ± 10.6 years). Monitoring devices were used regularly by 75.9% (n = 82) of caregivers, and most monitored daily/nightly. Frequently used devices were pulse oximeters (64.6%), baby monitors (64.6%), thermometers (24.1%), and Epi-Care (26.8%). Younger caregiver and patient age and history of status epilepticus were associated with increased use of monitoring, and 81% of monitor users reported having avoided a critical incident with nocturnal monitoring. The need for resuscitation due to cardiac or respiratory arrest was reported by 22 caregivers (20.4%), and most cases (72.7%) were associated with a seizure. Caregivers reported frequently performing interventions at night, including oropharyngeal suction, oxygenation, personal hygiene, and change of body position. Most caregivers were well informed about SUDEP (n = 102; 94%) and monitored for a lateral or supine body position; however, only 39.8% reported receiving resuscitation training, whereas 52.8% (n = 57) knew what to do in case the child's breathing or heart activity failed. Significance: Critical incidents and the need for resuscitation are reported frequently by caregivers and may be related to high mortality and SUDEP rates in DS. Resuscitation training is welcomed by caregivers and should be continuously provided. Oxygen monitoring devices are frequently used and considered useful by caregivers.
CRIS-Team Scopus Importer:2023-11-24
Keywords: encephalopathy; epilepsy; near-SUDEP; seizure